Peningkatan Kompetensi Pemeriksaan Telur Cacing pada Feses Sapi di SMK PP Wiyata Bakti - Roja Kurnia Noorshy; Fia Amalia; Nofan Rickyawan; Yose Iyya Amalia Kurniawan (Penerbit Goodwood, 2026)
Purpose: The goal of this study was to enhance students' knowledge and skills in identifying helminth eggs in cattle feces through structured teaching and hands-on laboratory practice, strengthening early parasitology-based disease detection abilities in vocational livestock education. Methodology/Approach: A pre-test-post-test design was used with 20 students from SMK PP Wiyata Bakti. Activities included lectures, PowerPoint presentations, posters, native fecal examination demonstrations, guided practice, and evaluations through post-tests and a Community Satisfaction Index. Data were analyzed descriptively. Results/Findings: The average test scores increased from 66.5% to 83%, indicating significant improvement in both concepts and procedures. Community Satisfaction Index (IKM) scores showed high satisfaction (75–90% “very satisfied”) regarding the material relevance, facilitator performance, and practical usefulness. Conclusions: Combining visual media with direct lab demonstrations effectively strengthened students' diagnostic abilities in parasitology, supporting the integration of helminth detection training into vocational livestock curricula. Limitations: The small sample size from a single institution limits broader applicability. Contributions: This study provides evidence that native fecal examination training enhances diagnostic competence and offers a replicable model for livestock health monitoring.